CrypTFlow2: Practical 2-Party Secure Inference - Rathee, Deevashwer; Rathee, Mayank; Kumar, Nishant; Chandran, Nishanth; Gupta, Divya; Rastogi, Aseem; Sharma, Rahul (27th Annual Conference on Computer and Communications Security (ACM CCS 2020), 2020)
We present CrypTFlow2, a cryptographic framework for secure inference over realistic Deep Neural Networks (DNNs) using secure 2-party computation. CrypTFlow2 protocols are both correct – i.e., their outputs are bitwise equivalent to the cleartext execution – and efficient – they outperform the state-of-the-art protocols in both latency and scale. At the core of CrypTFlow2, we have new 2PC protocols for secure comparison and division, designed carefully to balance round and communication complexity for secure inference tasks. Using CrypTFlow2, we present the first secure inference over ImageNet-scale DNNs like ResNet50 and DenseNet121. These DNNs are at least an order of magnitude larger than those considered in the prior work of 2-party DNN inference. Even on the benchmarks considered by prior work, CrypTFlow2 requires an order of magnitude less communication and 20×-30× less time than the state-of-the-art.